TRACING PERSIAN INFLUENCES: EXPLORING THE MEANING OF MOSQUES AND MAUSOLEUMS IN SOUTH SULAWESI AS ICONIC ISLAMIC ARCHITECTURE - Moh. Sutrisno (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2023)
This study explores the meaning of Mosques and Mausoleums in South Sulawesi as Islamic architecture influenced by Persian civilization. Previous research on the shape of the mausoleum scattered in South Sulawesi indicated the justification of Persian civilization. The research used a rationalistic paradigm with qualitative methods. The study's results explained that the meaning of mosques and mausoleums indicated the development of the spread of Islam in South Sulawesi. The old mosque has concluded as an iconic Islamic architecture in the category of Islamic heritage buildings. The Old Jami Mosque in Palopo, the al-Hilal Mosque of Katangka Gowa, and the old al-Mujahidin Mosque in Bone represent the three old mosques. The syntactic relations of the three regions were compiled in a historical relationship as the three great kingdoms in the classical period of Islam in South Sulawesi. The similarity aspect is shown by the alignment of the shape of the mosque with the architectural forms of the archipelago's mosques through the shape of the roof and its layers—shapes from nature such as leaves, mean fertility. The creativity of carving on the mihrab shows public awareness to present the mosque's beauty through calligraphy.